The Effect of Tax Socialization, E-Filling, Quality of Fiscal Services and Tax Sanctions on Taxpayer Compliance at the Tax Service Office (KPP) Pratama Pematang Siantar - Ananda Yesika Silaban (International Journal of Applied Finance and Business Studies, 2020)
This study aims to determine the socialization of taxation, e-filling, quality of tax services and tax sanctions on taxpayer compliance. This type of research is a quantitative research where the research location was conducted in Pematang Siantar City. The data collection was carried out using a questionnaire distributed to individual taxpayers registered at KPP Pratama Pematang Siantar as many as 100 respondents. Sampling was done using the Accidental Sampling method. Methods of data analysis using descriptive statistics, data quality testing, classical assumption test, multiple linear regression test and hypothesis testing. The results of this study are tax socialization variables, e-filling, quality of tax services and tax sanctions have a significant positive effect on taxpayer compliance. Partially, the tax socialization e-filling.